2012
DOI: 10.1139/f2012-118
|View full text |Cite
|
Sign up to set email alerts
|

Performance of farmed, hybrid, and wild Atlantic salmon (Salmo salar) families in a natural river environment

Abstract: Survival, growth, and diet were compared for farmed, hybrid, and wild Atlantic salmon (Salmo salar) families from the eyed egg to the smolt stage in River Guddalselva, Hardangerfjord, Norway. All individuals that survived until the smolt stage were captured in a Wolf trap and identified to one of the 69 experimental families using microsatellite markers. Survival of farmed salmon progeny was significantly lower than that of hybrids and wild progeny. However, survival varied considerably, from 0.17% to 6.4%, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
185
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 109 publications
(206 citation statements)
references
References 57 publications
17
185
4
Order By: Relevance
“…Intriguingly, found that within-family variation in body size of Atlantic salmon (measured in a hatchery setting) diminished with increasing generations of domestication (see also Solberg et al, 2013a). Under fully wild conditions, variance differences between wild, farmed and hybrid families may be largely unpredictable and context dependent, given that our findings did not match those of Skaala et al (2012) despite very similar study designs (but different genetic backgrounds). One possibility is that farmed fish may lose their environmental sensitivity (that is, degree to which their phenotypes or performance is buffeted by prevailing conditions) in hatchery environments, but not wild environments, as they are only selected in the former.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Intriguingly, found that within-family variation in body size of Atlantic salmon (measured in a hatchery setting) diminished with increasing generations of domestication (see also Solberg et al, 2013a). Under fully wild conditions, variance differences between wild, farmed and hybrid families may be largely unpredictable and context dependent, given that our findings did not match those of Skaala et al (2012) despite very similar study designs (but different genetic backgrounds). One possibility is that farmed fish may lose their environmental sensitivity (that is, degree to which their phenotypes or performance is buffeted by prevailing conditions) in hatchery environments, but not wild environments, as they are only selected in the former.…”
Section: Discussionmentioning
confidence: 63%
“…In a few samples, we did find variance heterogeneity but the patterns were inconsistent; for example, in the 1998 cohort electrofished 0+parr, survival variation was greatest among F 2 Hy families (perhaps due to rare advantageous recombinants), while for the 1993 and 1998 cohort trapped parr samples, variance in representation was highest for pure wild families and lowest for pure farm families (as one would predict if farm families are genetically depauperate), with hybrid families being generally intermediate. Although Skaala et al used Mowi strain salmon in one of their experimental cohorts, the Fanad Mowi strain used by us is likely to be divergent from theirs in its genetic make-up (because of lower broodstock numbers and a separate breeding programme); thus differences in genetic background and selection trajectories of the farm strains may explain the inconsistent results, in terms of variance in performance, between Skaala et al (2012) and this study. For offspring L F and mass, no heterogeneity in between-family variance was found (Supplementary Table S3), suggesting that each group had similar levels of additive genetic variance for these traits.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations